Introducción al sistema Vax-11 780 y operación y administración del sistema Vax-VMS - Jallath Coria, Eduardo S.; Jiménez García, Alejandro; Muñíz Zafra, Sócrates A.; Sánchez Sandoval, Humberto (My University, 1985)
The system manager must coordinate disk and tape management with the system´s users and operators. The system manager is responsible for deciding how the user data disk are initialized, mounted, backed up, and when necessary, verified. Although the system manager establishes the guidelines, the operators usually perform the actual operations. Data stored on mass-storage volumes must be organized so it can be retrieved quickly, and protected from access by unauthorized users. For this purpose, disks used on a VAX/VMS system are formatted according to the FILES-11 on-disk structure, and magnetic tapes comply with the ANSI Level 3 tape file standard.
Keywords: configuration; managing; users; resources; customizing